2002
DOI: 10.1002/syn.10086
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned‐fear stress increases Fos expression in monoaminergic and GABAergic neurons of the locus coeruleus and dorsal raphe nuclei

Abstract: Many studies have demonstrated that physical or psychological stress can increase Fos expression in brainstem monoaminergic nuclei. Little is known, however, about the extent to which stress increases the expression of Fos in monoaminergic and nonmonoaminergic neurons in the brainstem. We examined the effects of conditioned-fear (CF) stress following mild footshock (FS) as unconditioned stress on Fos expression in the monoaminergic and GABAergic neurons of the ventral tegmental area (VTA), locus coeruleus (LC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Central release of norepinephrine plays an important role in the reinforcement of fear memory likely through activation of b (Ferry and McGaugh, 1999) and a 1 ARs (Ferry et al, 1999b). It has been established that locus coeruleus noradrenergic neurons are activated by the US of the footshock (Ishida et al, 2002;Sara, 1985) as well as other stressful stimuli (Abercrombie and Jacobs, 1987). Activation of either the b 2 (Ferry and McGaugh, 1999) or a 1 (Ferry et al, 1999b) ARs increases attention and arousal, and enhances memory.…”
Section: Discussionmentioning
confidence: 99%
“…Central release of norepinephrine plays an important role in the reinforcement of fear memory likely through activation of b (Ferry and McGaugh, 1999) and a 1 ARs (Ferry et al, 1999b). It has been established that locus coeruleus noradrenergic neurons are activated by the US of the footshock (Ishida et al, 2002;Sara, 1985) as well as other stressful stimuli (Abercrombie and Jacobs, 1987). Activation of either the b 2 (Ferry and McGaugh, 1999) or a 1 (Ferry et al, 1999b) ARs increases attention and arousal, and enhances memory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diazepam would reduce the pressor response to the cold pressor test due to the augmentation of the GABAergic inhibition of the PVN. This model may also explain the differential effects of diazepam on the heat stressor-evoked and threat-evoked sweat gland responses, as whilst it is known that heat stressor activates the PVN (Cham et al 2006), anxiety, including that associated with conditioned fear, has been shown to lead to the activation of the LC both in experimental animals (Ishida et al 2002;Liu et al 2003) and humans (Liddell et al 2005). The importance of the distribution of the benzodiazepine sensitive and insensitive GABA A receptors in the pre-autonomic sympathetic circuitry is highlighted by the fact that the barbiturates, which, like the benzodiazepines, act by modulating GABA A receptors (Rudolph 2004) and also potentiate GABAergic responses in the LC (Chen et al 1999), are effective in antagonising the sympathetic activation of the pupil Sigg 1969, 1973).…”
Section: Effects Of Diazepam On Pupillary Reflexesmentioning
confidence: 95%
“…Increased locus coeruleus activity and norepinephrine release have also been correlated with processing of novel stimuli, learned fear, as well as social events such as mating and mother -infant interactions (Levy et al 1990;Aston-Jones et al 1991;Sara et al 1994;Wilson and Sullivan 1994;Keverne and Brennan 1996;Ishida et al 2002). In the main olfactory system, the noradrenergic system has been implicated in several types of learning, including infant attachment, nonassociative and associative conditioning, and habituation.…”
Section: Norepinephrinementioning
confidence: 99%